Designing a Web-Based Accounting Information System Using the Object Oriented Analysis and Design Method - Hasibuan, Anisha Fhuza; Alda, Muhamad (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The development of information technology in the digital era has created many new efficient applications. With the development of computer technology as a means of processing data into information which is then processed again in such a way in its presentation. Perum BULOG is one of the state-owned companies engaged in rice logistics and food security. As a company that continues to carry out public duties from the government, BULOG in carrying out activities that can stabilize the basic purchase price for grain, stabilize prices, especially basic prices, distribute rice for the poor (Raskin) and manage food stocks. This research aims to optimize the process of purchasing food and distributing computerized social assistance. The development method used in making this system is the Object Oriented Analysis and Design (OOAD) method which can model objects in the system, in the context of AIS, objects such as "accounts, transactions" can be represented as objects in the OOAD model. The results showed that the sales and distribution activities of social assistance are increasingly managed according to the needs equipped with a transaction process that can be stored.